What pops out in positional priming of pop-out: insights from event-related EEG lateralizations - Gokce, Ahu; Geyer, Thomas; Finke, Kathrin; Müller, Hermann J.; Töllner, Thomas (Frontiers in Psychology, 2014)
It is well established that, in visual pop-out search, reaction time (RT) performance is influenced by cross-trial repetitions versus changes of target-defining attributes. One instance of this is referred to as ‘positional priming of pop-out (pPoP)’ (Maljkovic & Nakayama, 1996). In positional PoP paradigms, the processing of the current target is examined depending on whether it occurs at the previous target or a previous distractor location, relative to a previously empty location (‘neutral’ baseline), permitting target facilitation and distractor inhibition to be dissociated. The present study combined RT measures with specific sensory- and motor-driven event-related lateralizations to track the time course of four distinct processing levels as a function of the target’s position across consecutive trials. The results showed that, relative to targets at previous target and ‘neutral’ locations, the appearance of a target at a previous distractor location was associated with a delayed build-up of the PCN wave, indicating that distractor positions are suppressed at early stages of visual processing. By contrast, presentation of a target at a previous target, relative to ‘neutral’ and distractor locations, modulated the elicitation of the subsequent sLRP wave, indicating that post-selective response selection is facilitated if the target occurred at the same position as on the previous trial. Overall, the results of present study provides electrophysiological evidence for the idea that target location priming (RT benefits) does not originate from an enhanced coding of target saliency at repeated (target) locations; instead, they arise (near-) exclusively from processing levels subsequent to focal-attentional target selection.